Multiple ALMT subunits combine to form functional anion channels: A case study for rice ALMT7 - Zhou, Hui; Hu, Zhuoran; Luo, Yunxin; Feng, Cuizhu; Long, Yu (Frontiers in Plant Science, 2022)
The Aluminum Activated Malate Transporter (ALMT) family members are anion channels that play important roles in organic acid transport, stress resistance, growth, development, fertilization and GABA responses. The rice malate permeable OsALMT7 influences panicle development and grain yield. A truncated OsALMT7 mutant, panicle apical abortion1 (paab1) lacking at least 2 transmembrane helices, mediates reduced malate efflux resulting in yield reducing. Here, we further investigated the contribution of OsALMT7 transmembrane helices to channel activity, using heterologous expression in Xenopus laevis oocytes. We further found that OsALMT7 formed as a homomer by co-expressing OsALMT7 and paab1 proteins in oocytes and detecting the physical interaction between two OsALMT7, and between OsALMT7 and paab1 mutant protein. Further study proved that not just OsALMT7, mutants of TaALMT1 inhibit wild-type TaALMT1 channel, indicating that ALMTs might perform channel function as homomers. Our discovery brings a light for ion channel structure and homomultimer regulation understanding for ALMT anion channels and potential for crop grain yield and stress response improvement in the context of the essential role of ALMTs in these plant processes.